CAUSES AND SOLUTIONS TO THE LACK OF WATER SUPPLY IN INDONESIAN URBAN - Pah, Jusuf J. S. (Jurnal Teknik Sipil, 2011)
ABSTRACTThis study aimed at finding key factors which cause lack of water supply in Indonesianurban and develop the key factors which solve it. Relevant literatures bearing on theissue of urban water supply were studied. The city of Jakarta was taken asrepresentative of Indonesian urban. For the purpose of finding the causes anddeveloping the related solutions, relevant data bearing to the city’s water supply systemwere analysed. It was found that the lack of water supply in urban areas manifests in theexceeding of water demand over supply, low piped-water coverage, and intermittencyof water supply; whereas poor governance and low water tariff are the root factor whichcause them. Consequently good governance and higher water tariff were proposed asthe solutions to the problem. It also showed that the perception that urban poor cannotafford to pay water at full price, is but mythical.